(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2007)
Patterns of lead ions accumulation and localization, and their influence on the physiological and biochemical parameters in shoots of aquatic moss Fontinalis antipyretica are investigated. The ability of F. antipyretica to bind lead ions on the surface of leaf plates is revealed. Increase of content of TBA-reactive substances and carbonylproteins is observed in moss under metal treatment. Lead was found to induce an increase of activity of superoxide dismutase, catalase, glutathione peroxidase, glutathione reductase with rising the glutathione content.